Reliability, Validity and Factor Structure of the Persian Translation of General Health Questionnire (GHQ-28) in Hospitals of Kerman University of Medical Sciences - M Nazifi; HR Mokarami; AK Akbaritabar; M Faraji Kujerdi; R Tabrizi; A Rahi (Fasa University of Medical Sciences, 2013)
Background & Objective: The 28-item General Health Questionnaire (GHQ-28) consists of 4 subscales.Validation of this questionnaire has been carried out by several studies conducted in Iran. Despite the multiplicity of researches which investigated the sensitivity, specificity and reliability of this questionnaire in Iran, few studies have investigated its factor structure. However, it is important to consider if Persian translations of GHQ-28 will indicate the same 4 factors as demonstrated in forign investigations. the aim of the current research was to assess the reliability, validity and the factor structure of the Persian version of GHQ-28.Materials & Methods: The current study was designed based on a survey method. A sample of 415 employees in Kerman hospitals participated in this study and completed the questionnaires.Results: The results showed that GHQ has an appropriate internal consistency for assessing the general health in this sample. Factor analysis using principal component method identified 4 factors in participants' responses, and these 4 factors accounted for 60% of the total variance. The correlation between GHQ total scores and the Pitsburg sleep quality index was significant at a level smaller than 0.001.Conclusion: According to the evidence of this research it is concluded that explorative factor analysis identifies four factors in the participants' responses and the fact that this questionnire has an appropriate internal consistency and an adequate validity for the assessment of general health in this sample.